Phase engineering of a multiphasic 1T/2H MoS2 catalyst for highly efficient hydrogen evolution. Issue 6 (18th January 2017) - Wang, Dezhi; Zhang, Xiangyong; Bao, Siyuan; Zhang, Zhongting; Fei, Hao; Wu, Zhuangzhi
Abstract : A multiphasic 1T/2H MoS2 electrocatalyst for hydrogen evolution, which exhibits excellent performances with a small Tafel slope of 46 mV dec −1, is developed by phase engineering via a simple hydrothermal route. Abstract : Molybdenum disulfide (MoS2 ) has attracted much attention as a promising electrocatalyst for the hydrogen evolution reaction (HER). Although tremendous efforts have been made to enhance the HER performance of MoS2, the functional design of its intrinsic structures still remains challenging. In this work, a highly active and stable multiphasic catalyst (1T/2H MoS2 ) is developed through a facile hydrothermal route, in which the 1T phase is induced by the intercalation of guest ions and molecules, and the concentration of the 1T phase can be controlled by adjusting the preparation temperature. The existence of the 1T phase provides more active sites and better conductivity for the HER, resulting in an excellent activity with a small Tafel slope of 46 mV dec −1 . More importantly, the integration with the 2H phase is beneficial to the stabilization of the metastable 1T phase, ensuring the excellent durability of 1T/2H MoS2 .